Synaptic activity is not required for establishing heterogeneity of inner hair cell ribbon synapses - Karagulyan, Nare; Moser, Tobias (Frontiers in Molecular Neuroscience, 2023)
Neural sound encoding in the mammalian cochlea faces the challenge of representing audible sound pressures that vary over six orders of magnitude. The cochlea meets this demand through the use of active micromechanics as well as the diversity and adaptation of afferent neurons and their synapses. Mechanisms underlying neural diversity likely include heterogeneous presynaptic input from inner hair cells (IHCs) to spiral ganglion neurons (SGNs) as well as differences in the molecular profile of SGNs and in their efferent control. Here, we tested whether glutamate release from IHCs, previously found to be critical for maintaining different molecular SGN profiles, is required for establishing heterogeneity of active zones (AZs) in IHCs. We analyzed structural and functional heterogeneity of IHC AZs in mouse mutants with disrupted glutamate release from IHCs due to lack of a vesicular glutamate transporter (Vglut3) or impaired exocytosis due to defective otoferlin. We found the variance of the voltage-dependence of presynaptic Ca2+ influx to be reduced in exocytosis-deficient IHCs of otoferlin mutants. Yet, the spatial gradients of maximal amplitude and voltage-dependence of Ca2+ influx along the pillar-modiolar IHC axis were maintained in both mutants. Further immunohistochemical analysis showed an intact spatial gradient of ribbon size in Vglut3–/– mice. These results indicate that IHC exocytosis and glutamate release are not strictly required for establishing the heterogeneity of IHC AZs.